The effect of conditioned media on the cellular proliferation of pancreatic cancer cells, pancreatic stellate cells, and myeloid-derived suppressor cells - Y. Chong; S. Samsudin; D. Bahrani; C. Chang; A. Masamune; S. Ng; N. Ismail; K. Ho (World Cancer Research Journal)
Objective: Pancreatic cancer has remained one of the most devastating diseases over the past two decades, with minimal improvements in survival rates. Its highly immunosuppressive tumour microenvironment is driven by secreted proteins, such as cytokines and growth factors, which promote the differentiation of immunosuppressive cells and influence cellular proliferation and migration. This study investigates how the secretome from pancreatic cancer and pancreatic stellate cells affects the proliferation of myeloid-derived suppressor cells and its implications for cellular proliferation.